Pengaruh Perceived Ease of Use, Brand Trust dan Customer Experience Terhadap Minat Pengguna Maxim diKota Medan - Salsabillah Eka Zulnawati; Yuli Arnida Pohan (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of Perceived Ease of Use, Brand Trust, and Customer Experience on Users’ Interest in Maxim in Medan City using a quantitative method with purposive sampling, involving 120 respondents determined through the Lemeshow formula. Data were collected through questionnaires and analyzed with SPSS software. The results indicate that Perceived Ease of Use (t-count 2.784 > t-table 1.980; sig. 0.006 < 0.05), Brand Trust (t-count 2.063 > t-table 1.980; sig. 0.041 < 0.05), and Customer Experience (t-count 5.323 > t-table 1.980; sig. 0.000 < 0.05) each have a positive and significant effect on Users’ Interest in Maxim in Medan City. Furthermore, the F-test results demonstrate that all three variables simultaneously exert a positive and significant influence on Users’ Interest in Maxim in Medan City.